Study of the role of transmembrane emp24 domain-containing protein 2 in oral squamous cell carcinoma - RUAN Zhao-wei; JIAO Xue-feng; XIAO Gao-tian; CHEN Jin-ling; LI Jun; LV Shu-ying (Journal of Applied Oral Science)
Abstract Objective This study aimed to investigate the role of transmembrane emp24 domain-containing protein 2 (TMED2) in oral squamous cell carcinoma (OSCC). Methodology A bioinformatics analysis was first conducted to explore TMED2 expression in OSCC and its relation with overall survival. The analysis results were further verified by assessing TMED2 expression levels in human normal oral keratinocyte cells and human OSCC cell lines using quantitative real-time polymerase chain reaction and the Western blot. Finally, the effects of TMED2 knockdown and overexpression on the expression levels of TMED2, ADP-ribosylation factor 1, extracellular signal-regulated kinase ½, and phospho-extracellular signal-regulated kinase ½ proteins were examined in cells using the Western blot. Results The GEPIA2 database showed that OSCC tissues expressed more TMED2 than normal tissues. At the cellular level, TMED2 expression significantly increased in SCC-4, HSC-3, and CAL-27 cells than in human normal oral keratinocyte cells. TMED2 knockdown reduced cell proliferation, increased the apoptosis rate in SCC-4 cells, and led to a higher proportion of cells in the G0/G1 phase and a lower proportion in the S phase. Conclusion TMED2 may promote OSCC cell proliferation and inhibit apoptosis, potentially by activation of the ADP-ribosylation factor 1/ extracellular signal-regulated kinase ½ signaling pathway.